The Effect of Acetone Papaya Leaves Extract (Carica papaya, L.) to Hepatoprotector of Rat (Rattus novergicus) Induced by Paracetamol - Dewantari Saputri; Suyatmi .; Kusmadewi Eka Damayanti (Fakultas Kedokteran Universitas Sebelas Maret Surakarta, 2014)
Background: Acetone papaya leaves extract contains chlorophyll and flavonoids with antioxidative capacity to protect the liver cell from free radicals The aims of this research were to know the hepatoprotective effect of the extract and to investigate the influence of increasing dose of the extract towards the amount of paracetamol-induced liver cells damage of rats. Methods: This study was a laboratory experimental research applying posttest only controlled group design. A total of 24 Strain Wistar rats were equally divided into 6 groups. Rats for control group (KK) and 1st group (KP1) were given aquades for 7 days. The second treatment group (KP2) was given 100mg/kg body weight (bw) of rat dose curcuma tablet. The 3rd (KP3), 4th(KP4), and 5th (KP5) treatment groups ware given acetone papaya leaves extract dose 150mg/kg bw, 300mg/kg bw, 600mg/kg bw, respectively for 7 days. Paracetamol was given to KP1, KP2, KP3, KP4, KP5 with dose 600mg/kg weight of rat on 5th, 6th, and 7th day. Finally on 8th day, rat were sacrificed by neck dislocation. After that, we made histological slides from the liver that stained with Hematoxillin Eosin (HE). The slides were observed and assessed based on the liver histological damage (pyknosis, karyorrhexis and karyolysis). Data were analized by Kruskal Wallis (? = 0,05), and continued by Mann Whithney test(? = 0,05). Results: Kruskal Wallis showed that there was a significant difference between 6 groups. Result of Mann Whithney method showed that there was a significant difference between control group (KK)and treatment group (KP1, KP2,KP4,KP5) as well as between curcuma (KP2) and acetone papaya leaves extract (KP3,KP4, KP5) groups, but there was no any significant difference between groups the increase doses (KP3-KP4,KP5). Conclusion: Acetone papaya leaves extract has hepatoprotective effect to the liver cell histological damage of rats induced by paracetamol.. Key words : acetone papaya leaves extract, paracetamol, liver cell histological damage.